Venous thromboembolism in otolaryngology surgical inpatients receiving chemoprophylaxis. Issue 8 (27th November 2013) - Yarlagadda, Bharat B.; Brook, Christopher D.; Stein, Daniel J.; Jalisi, Scharukh
Abstract Background The Caprini risk assessment model for stratifying patients' risk for venous thromboembolism (VTE) has been validated in the otolaryngology literature. We sought to determine the incidence of VTE in patients receiving chemoprophylaxis and correlate with the Caprini risk assessment model. Methods A retrospective chart review of adult surgical admissions to an academic otolaryngology service from 2007 to 2012 was performed. Caprini risk assessment model scores were calculated and compared to incidence of VTE based on diagnosis codes. Results Seven hundred four patients met our inclusion criteria. Fifteen (2.13%) developed VTE. The Caprini risk assessment model score averaged 5.7 (range, 2–16). Patients with VTE had an average score of 9.87 versus 5.62 for those without (p < .0001). No patients with a score of 6 and below, 3.01% with 7‐8, and 13.16% with a score >9 developed VTE. Conclusion The incidence of VTE increases with Caprini risk assessment model score, and a score of >8 predicts a high risk (>13%) of VTE in postoperative otolaryngology inpatients despite chemoprophylaxis. © 2013 Wiley Periodicals, Inc. Head Neck 36: 1087–1093, 2014